Application of The Reverse Engineering In The Modelling of A Blade and Screen In A Hammer Mill - Annisa Haq; Agus Kusnayat; Sri Martini (School of Industrial and System Engineering, Telkom University, 2023)
PT XYZ plans to produce coconut shell briquettes. Currently, PT XYZ already has a hammer millmachine that will be used in the production process. A hammer mill machine is a machine that servesto smooth the material. Before carrying out mass production, a simulation is carried out first. Themanufacture of briquettes found obstacles in the process of grinding and screening. Coconut shellcharcoal that has been milled and entered is partially retained and cannot be released to proceed to thenext process. The grinding result is larger than the screen size, which is 1 to 2 mm. In the manufactureof briquettes, it is expected that the grinding results are less or equal to 0.4 mm. Based on theidentification of the problem, the alternative solution chosen by the researcher is to redesign thehammer mill machine, especially on the blade and screen sections. The design is done using thereverse engineering method. There are five steps in designing using this method. In the study, it wasfound that the second design was a suitable design to be developed because it was better than theexisting state. The mill results were obtained with an average of 0.0343 mm and a grinding time of186.807 seconds. The fineness values and the grinding process time were obtained throughsimulations using the EDEM 2022.1 software.